PELANGGENGAN WACANA DOMINAN DALAM NOVEL ANAK GEMBALA YANG TERTIDUR PANJANG DI AKHIR ZAMAN (2019) - Farobi Fatkhurridho (JURNAL ILMU BUDAYA, 2022)
People's attitudes toward national discourse do not grow without cause but are regulated and reproduced by the ruling authorities. Nationalism is never stable due to the reproduction of ideology.  This practice was later called The Regime of Truth by Michael Foucault. The regime regulates views and how people pay attention to the dichotomy of right and wrong, which later develops as a dominant discourse. Anak Gembala yang Tertidur Panjang di Akhir Zaman (2019) by A. Mustafa is a novel that describes how dominant discourse is perpetuated. The novel, set during the Orde Baru era, describes how the dominant power repressed and discriminated against the lives of Queer and Ahmadiyyah. Through the speech acts of the characters in the book, this study will try to break down how the dominant discourse keeps going in the cycle of truth regimes.